2021
DOI: 10.3390/parasitologia1030015
|View full text |Cite
|
Sign up to set email alerts
|

Surveillance of Host-Seeking Ticks in the Flint Hills Region (USA) and Associations with Environmental Determinants

Abstract: Diversity and phenology of host-seeking ticks were studied in the Flint Hills region of the USA, which is a prominent region for raising beef cattle. Between a two-year period from 2015–2017, ticks were collected using the dragging method from 9 distant locations, 6 of which were studied seasonally and 3 continuously throughout the study period. Of the 10,055 ticks collected, 76.5% were the Lonestar tick (Amblyomma americanum), 14% were American dog tick (Dermacentor variabilis), and 9.1% were Gulf Coast tick … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
9
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 6 publications
(9 citation statements)
references
References 35 publications
0
9
0
Order By: Relevance
“…We identified five tick species of public health importance. Previous studies conducted at sites near, and including some of our sites, have identified much the same set of species [ 4 , 10 , 17 19 ]. Amblyomma americanum was the most abundant, comprising approximately 97% of all individual ticks collected.…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations
“…We identified five tick species of public health importance. Previous studies conducted at sites near, and including some of our sites, have identified much the same set of species [ 4 , 10 , 17 19 ]. Amblyomma americanum was the most abundant, comprising approximately 97% of all individual ticks collected.…”
Section: Discussionmentioning
confidence: 99%
“…americanum activities with the historical questing patterns [ 25 , 26 ], shows a general earlier shift in peak timings of up to 2 months across the sites. The changes in peak timings could be attributed in part to warming climate [ 10 ], which has been associated with north-and-westward ranges expansion of the tick [ 27 – 30 ]. Phenology studies in warmer southeastern parts of United States have reported peak activity between March and April for A .…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…According to research findings, A. americanum may be infected with the BRBV at the larva or nymph stages ( Spare et al, 2021 ; Aziati et al, 2022 ). Multiple BRBV detections in A. americanum indicate that these viruses have similar life cycles and routes of transmission ( Miller, 2018 ; Savage et al, 2018 ).…”
Section: Bourbon Virusmentioning
confidence: 99%